2004
DOI: 10.5483/bmbrep.2004.37.3.320
|View full text |Cite
|
Sign up to set email alerts
|

Homeodomain-leucine Zipper Proteins Interact with a Plant Homologue of the Transcriptional Co-activator Multiprotein Bridging Factor 1

Abstract: StMBF1 (Solanum tuberosum multiprotein bridging factor 1) is a plant member of the MBF1 family of transcriptional co-activators. In an attempt to understand the role of StMBF1, we analyzed its interaction with plant transcription factors of the homeodomain-leucine zipper (Hd-Zip) family, a group of proteins with a typical leucine zipper motif adjacent to a homeodomain. StMBF1 is able to interact in vitro with the Hd-Zip protein Hahb-4 both in the presence and absence of DNA. Upon binding, StMBF1 increases the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Additional support to the importance of the CTR was provided by Sakuma et al [36]; they identified that the recessive allele vrs1 , which causes the six-rowed phenotype in barley, encodes an HD-Zip I TF 14 residues shorter in the CTR than its paralogous gene HvHox2 (both share 88% of identity in the whole protein), which was caused by a 300-bp insertion that introduced a stop codon. These authors identified a conserved motif within these 14 amino acids and suggested that this motif could interact with certain classes of co-activators in order to exert its biological function [36,37]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional support to the importance of the CTR was provided by Sakuma et al [36]; they identified that the recessive allele vrs1 , which causes the six-rowed phenotype in barley, encodes an HD-Zip I TF 14 residues shorter in the CTR than its paralogous gene HvHox2 (both share 88% of identity in the whole protein), which was caused by a 300-bp insertion that introduced a stop codon. These authors identified a conserved motif within these 14 amino acids and suggested that this motif could interact with certain classes of co-activators in order to exert its biological function [36,37]. …”
Section: Discussionmentioning
confidence: 99%
“…Good examples of the importance of this regions are VRS1 [36], which lacks a motif in the CTR in relation to HvHox2, and the protein without the last 14 residues of the CTR that mimics the tl mutation [38]; in both cases the deletions correspond to AHA-like sequences. Finally, the different versions of AHA motifs found, shared by the members of each group, may be responsible for the interaction with different co-activators or members of the basal transcriptional machinery [37], and thus provide a source of functional divergence among HD-Zip I proteins together with differential expression patterns in some cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the motif 8 is not annotated in the protein family (Pfam) database (http://pfam.sanger.ac.uk/), but its loss may be sufficient to differentiate the functions of the Vrs1 and HvHox2 gene products. Transcriptional co-activators enhance transcription by interacting with both general and gene-specific transcription factors (Zanetti et al 2004). Thus, motif 8 in HvHOX2 could interact with certain classes of transcriptional co-activators, and then act as an activator for the transcription of downstream genes, while VRS1 would not be able to replicate this interaction as it lacks motif 8.…”
Section: Discussionmentioning
confidence: 99%
“…Established interactions between MBF1 and members of the former family are FTZ-F1, Ad4BP (adrenal 4-binding protein; a human orthologue of FTZ-F1), and liver receptor homologue 1, liver X receptor α and PPARγ (peroxisome-proliferator-activated receptor γ ), non-steroid nuclear receptors, involved in lipid metabolism in humans [3,[5][6][7]25]. Known interaction partners belonging to the bZIP family include GCN4 (general control non-derepressible 4), CREB (cAMP-response-element-binding protein) and CREB1, ATF (activating transcription factor) 1, Jun and Fos, TDF (tracheae defective factor) and HaHB4 (Helianthus annuus homeobox-leucine zipper protein 4) [12,21,24,25,28,29]. Jun, Fos and ATF family members dimerize into homo-or hetero-dimers, all called AP-1 (activator protein 1).…”
Section: Transcription Activationmentioning
confidence: 99%